Perancangan Learning Management System menggunakan Metode Design Thinking (Studi Kasus: SMK Prajnaparamita Malang) - Anggi Riza Amirullah Sidharta; Retno Indah Rokhmawati; Diah Priharsari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
SMK Prajnaparamita Malang is a private vocational school that has expertise programs in hospitality accommodation, beauty and pharmacy. During the pandemic, this SMK must carry out the online teaching and learning process using several learning platforms at once. The use of multiple platforms at once makes it difficult for teachers and students because they have to adapt to the platforms used. This study aims to design a user experience of a learning management system that contains all the features of the platform that was previously used using the Design Thinking Method. Design Thinking has 5 stages, namely Empathize, Define, Ideate, Prototype and Test. The solution design that has been made will then be tested using the Post-Study System Usability Questionnaire (PSSUQ) to determine the usability value of the user interface design created by the researcher. The purpose of making this PSSUQ questionnaire is to find out what users feel after using the solution design and whether the solution design has solved the user's problem. The results of the Post-Study System Usability Questionnaire (PSSUQ) resulted in a score on the overall subscale obtained a score of 1.81, system usability obtained a value of 1.87, information quality obtained a value of 1.97 and interface quality obtained a value of 1.49. This value indicates if the system is good and satisfies the user in terms of usability, information quality and the quality of the user interface display.